Genetic Evolution of Glioblastoma Stem-Like Cells From Primary to Recurrent Tumor. (29th September 2017) - Orzan, Francesca; De Bacco, Francesca; Crisafulli, Giovanni; Pellegatta, Serena; Mussolin, Benedetta; Siravegna, Giulia; D'Ambrosio, Antonio; Comoglio, Paolo M.; Finocchiaro, Gaetano; Boccaccio, Carla
Abstract : Glioblastoma (GBM) is a lethal tumor that displays remarkable genetic heterogeneity. It is also known that GBM contains a cell hierarchy driven by GBM stem-like cells (GSCs), responsible for tumor generation, therapeutic resistance, and relapse. An important and still open issue is whether phylogenetically related GSCs can be found in matched primary and recurrent GBMs, and reflect tumor genetic evolution under therapeutic pressure. To address this, we analyzed the mutational profile of GSCs isolated from either human primary GBMs (primary GSCs) or their matched tumors recurring after surgery and chemoradiotherapy (recurrent GSCs). We found that recurrent GSCs can accumulate temozolomide-related mutations over primary GSCs, following both linear and branched patterns. In the latter case, primary and recurrent GSCs share a common set of lesions, but also harbor distinctive mutations indicating that primary and recurrent GSCs derive from a putative common ancestor GSC by divergent genetic evolution. Interestingly, TP53 mutations distinctive of recurrent GSCs were detectable at low frequency in the corresponding primary tumors and likely marked pre-existent subclones that evolved under therapeutic pressure and expanded in the relapsing tumor. Consistently, recurrent GSCs displayed in vitro greater therapeutic resistance than primary GSCs. Overall, these data indicate that (a) phylogenetically related GSCs are found in matched primary and recurrent GBMs and (b) recurrent GSCs likely pre-exist in the untreated primary tumor and are both mutagenized and positively selected by chemoradiotherapy.